Athen, Griechenland. Aufarbeitung der Geschichte des DAI Athen. Die Arbeiten des Jahres 2017 - Kankeleit, Alexandra (e-Forschungsberichte des DAI, 2018)
In July 2016 the project “Reappraising the History of the DAI Athens during the National Socialist Era” began. The research in both German and Greek archives offers insight into an historical epoch from which we are now divided by over two generations. The focus is on concrete events and activities, but also personal feelings and experiences which can provide information about the role of the German Archaeological Institute in Athens. The following essay sheds light on a topic that until now has barely been the subject of research: the handing back of the DAI premises in 1950–1951 following the end of the occupation and the Greek Civil War.